(untitled) (Journal of the College of Education for Women, 2021)
Almost human societies are not void of poverty, as the latter accompanied the emergence of humanity, and it, thus, represents an eternal problem. To advance an individual’s reality and raise the level of the poor social classes, social security networks have been established. Such networks operate in society following social systems and laws to provide food, and material support. Besides, such networks help to rehabilitate the individual academically and vocationally. They empower vulnerable groups through the establishment of courses and workshop, provide (conditional) subsidies related to the health and educational aspects in order to achieve the sustainable development goals of (2030), and apply developmental roles of social safety nets that target the needy and poor groups living in slums, especially in the city of Baghdad. They further stand on the humanitarian and social conditions experienced by the residents of those areas. the study also examines the role of both formal and informal organizations in achieving sustainable development goals. The data of the study involves five complexes in Baghdad, specifically Al- Karkh side; these include the following: (Mu’amel Al-Masdar Complex, Al-Rahman Complex, Noor Complex), Al-Huda, Al-Raja’ Complex, and Al-Noor Village Complex). That is, the number of families was 250; 50 from each complex. A statistical program (SPSS) and scientific tools have been used to collect the data, such as observational questionnaire, interview, and groups focal point. The study has revealed that most of the respondents received food aids from different parties at a rate of (64.80%), especially during the crises that the country witnessed. The vast majority of the respondents, (1-87%), who benefited from the social assistance, do not have an alternative financial source.